Arbeit als Hoffnung. Jüdische Ghettos in Litauen 1941-1944 - Tauber, Joachim (Quellen und Darstellungen zur Zeitgeschichte, 2015)
In the ghettos of Lithuania an urban infrastructure developed based on the needs of Jewish conscription and forced labor for German occupation forces and the Lithuanian administration. Using the example of the ghettos in Vilnius, Kaunas, and Siauliai, the author reveals for the first time the ways to which Jewish labor conscription was organized inside and outside the ghettos and the patterns of daily ghetto life as seen by the inhabitants.